Recent trends in the analysis of vitamin D and its metabolites in milk – A review. (15th March 2015) - Kasalová, Eva; Aufartová, Jana; Krčmová, Lenka Kujovská; Solichová, Dagmar; Solich, Petr
Highlights: Review outlines methodologies used for the determination of vitamin D in milk. Vitamin D analysis methods in human and bovine milk were included. Various schemes of sample preparation, derivatisation and detection were reviewed. Summary of all LC methods which has not been written till now is presented Abstract: Vitamin D plays an important role in calcium metabolism and affects other metabolic pathways. Despite the intense interest in vitamin D, no comprehensive overview addressing the analysis of vitamin D in milk has been published. Historically, immunoassay techniques have been mainly used for the routine quantification of vitamin D and its metabolites. However, the greater accuracy and precision of chromatography makes it one of the most important methods in the analysis of vitamin D. The determination of vitamin D and its metabolites by LC–MS is the gold standard for its assessment. LC–MS has unique advantages for vitamin D determination and quantification due to its high sensitivity and specificity. In this review, the current status of vitamin D and its metabolites analysis in milk, human and bovine, including sample pre-treatment and chromatography analysis, are critically discussed and summarised.